2007
DOI: 10.1900/rds.2007.4.159
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Cardiomyopathy in OVE26 Mice Shows Mitochondrial ROS Production and Divergence Between In Vivo and In Vitro Contractility

Abstract: ■ AbstractMany diabetic patients suffer from a cardiomyopathy that cannot be explained solely by poor coronary perfusion. This cardiomyopathy may be due to either organ-based damage like fibrosis, or to direct damage to cardiomyocytes. Mitochondrial-derived reactive oxygen species (ROS) have been proposed to contribute to this cardiomyopathy. To address these questions, we used the OVE26 mouse model of severe type 1 diabetes to measure contractility in isolated cardiomyocytes by edge detection and in vivo with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…Model name/parameter C57Bl/6J + STZ FVB/N + STZ OVE26 Akita Apoptosis ↑ Increased (Xu et al 2013) ↑ Increased (Wold et al 2006) ↑ Increased (Xie et al 2011, Xu et al 2013) Oxidative stress ↑ Increased (Kuramoto et al 2014, Westermann et al 2009, Xu et al 2013, Yan et al 2015 ↑ Increased (Wold et al 2006) ↑ Increased (Liang et al 2002, Ye et al 2004, Song et al 2007, Wang et al 2013, Xu et al 2013 Unchanged (Bugger et al 2008) Calcium mobilisation ↓ Decreased (Wold et al 2006) ↓ Decreased (Ye et al 2004, Kralik et al 2005 ↓ Decreased (Lu et al 2007, Bugger et al 2009, Mishra et al 2010, LaRocca et al 2012, Prathipati et al 2016 …”
Section: ) Cardiac Lipidsmentioning
confidence: 99%
“…Model name/parameter C57Bl/6J + STZ FVB/N + STZ OVE26 Akita Apoptosis ↑ Increased (Xu et al 2013) ↑ Increased (Wold et al 2006) ↑ Increased (Xie et al 2011, Xu et al 2013) Oxidative stress ↑ Increased (Kuramoto et al 2014, Westermann et al 2009, Xu et al 2013, Yan et al 2015 ↑ Increased (Wold et al 2006) ↑ Increased (Liang et al 2002, Ye et al 2004, Song et al 2007, Wang et al 2013, Xu et al 2013 Unchanged (Bugger et al 2008) Calcium mobilisation ↓ Decreased (Wold et al 2006) ↓ Decreased (Ye et al 2004, Kralik et al 2005 ↓ Decreased (Lu et al 2007, Bugger et al 2009, Mishra et al 2010, LaRocca et al 2012, Prathipati et al 2016 …”
Section: ) Cardiac Lipidsmentioning
confidence: 99%
“…Interestingly, a recent report has also shown that the development of cardiomyopathy, in the STZ female rat is more rapid than in the aged-matched male (Moore, et al, 2014); mirroring the human diabetic female predisposition to a higher mortality as described in the introduction. In addition to the STZ/alloxan models there are several genetically derived T1DM mouse models such as the Akita mouse (Ins2 Akita ) and the OVE26 mouse (Song, Du, Prabhu, & Epstein, 2007). The Akita mouse phenotype is characterised by only diastolic dysfunction (LaRocca, et al, 2012) whereas the OVE26 mouse exhibits impaired diastolic and systolic dysfunction.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These mice were genetically engineered to carry a calmodulin minigene regulated by the rat insulin II promoter, with a fivefold increase in the content of calmodulin in ␤-cells (20,38,53). These OVE26 mice normally develop severe diabetes around 2 wk after birth, and they develop typical features of diabetic nephropathy and cardiomyopathy at 5 mo or older (20,38,53). Animals were euthanized at 3.5 mo after the onset of diabetes.…”
Section: Animal Modelsmentioning
confidence: 99%